TERHADAP KEPUTUSAN NASABAH DALAM MEMILIH JASA PERBANKAN PADA PT. BANK BRI CABANG MATARAM - Krisnawaty, Baiq Noviana (Jurnal Magister Manajemen, 2016)
This study aims to determine the effect of the elements of corporate image that is personality, reputation, value, and corporate and analyze the variables that have a dominant influence on the customer’s decision in choosing banking services at PT. Bank BRI Cabang Mataram. This research is expected to provide benefits such as: Academically, the requirement for unanimity courses Masters (S2) in the Management Program, University of Mataram. Theoretically, this study is one opportunity to apply the knowledge acquired during the Marketing Management in college. In practical terms, the expected results of the study can be used as consideration for PT. Bank BRI Cabang Mataram to promote the company. This type of research is associative causal research and sampling techniques using accidental sampling as many as 100 customers of Bank BRI Cabang Mataram. Analysis techniques used is Multiple Linear Regression. The results showed that: personality significantly influence the customer’s decision. Reputation significantly influence the customer’s decision. Value significantly influence the customer’s decision. corporate significantly influence the customer’s decision. The dominant variables strongly influence the customer’s decision that personality factors BRI Bank Cabang Mataram. Overall personality, reputation, value, and corporate significantly influence the customer’s decision. Then, the most important thing and should not be overlooked is that in a business, especially PT. Bank BRI Cabang Mataram is idealism product or performance that must be constantly maintained and improved. Because this is what distinguishes between other Cabang Bank BRI Unit and Other Bank. Keywords: Decision of customers, Elements of corporate image.